Results of certification audit in Mexican hospitals, a review from 2009 to 2012 - Ángel Fernando Galván-García; José de Jesús Vértiz-Ramírez; Alma Lucila Sauceda-Valenzuela; Ofelia Poblano-Verástegui; Enrique Ruelas-Barajas; Mario Salvador Sánchez-Domínguez (Instituto Nacional de Salud Pública, 2018)
Objective. To analyze the participation of Mexican hospitals in the certification process (equivalent to accreditation in other countries). Materials and methods. Crosssectional study that analyzes results of 136 establishments audited between 2009 and 2012. Standards with an excellent rating (9.0-10.0), approving (6-8.9) and non-approving (0-5.9) were identified. With a multinomial model, the probability of obtaining non-approving, approving and excellent qualification was calculated. Results. The general average score was 7.72, higher in ambulatory surgery centers (9.10), than in general hospitals (7.30) and specialty hospitals (7.99). All public establishments obtained an approval score. Hospitals audited in 2011 had a higher risk of obtaining an approval (RRR= 4.6, p<0.05) and excellent (RRR= 6.6, p<0.05) rating. Conclusions. The scope of the certification process in Mexico has been limited, with greater participation of the private sector. The evaluation certificate applied in 2011 favored the achievement of approval and excellence results. We recommend homologating the entire process with that of the Joint Commission International JCI.